An experimental investigation on the secondary breakup of carboxymethyl cellulose droplets. (March 2021) - Qian, Lijuan; Zhong, Xiaokai; Zhu, Chenlin; Lin, Jianzhong
Highlights: The secondary breakup of CMC droplets in a continuous air jet flow is studied. The effects of Weber number and effective Ohnesorge number on deformation characteristics are obtained. The prediction of CMC droplet breakup modes is based on Rayleigh-Taylor instability. Abstract: Secondary breakup is a common phenomenon in nature, as well as in industrial applications. The secondary breakup of Carboxymethyl cellulose (CMC) droplets in a continuous air jet flow is investigated experimentally by a high-speed digital camera. Through varying the Weber number and the Ohnesorge number in the experiment, the breakup morphology, deformation stage, and breakup regime map are discussed in detail. The results show that the breakup modes of CMC droplet are consistent with that of water droplets in the Weber number range from 8 to 50 considered in the experiment. The number of nodes generated at the toroidal rim of the CMC droplet is verified to be the same as that of water droplet, following "the combined R-T/aerodynamic drag" mechanism. However, the breakup results of CMC droplets and water droplets are significantly different. The liquid ring and nodes produced by CMC droplets cannot disintegrate completely under the action of aerodynamic forces. In different breakup modes, the effective Ohnesorge number of CMC droplets has different influences on the cross stream diameter time-wise evolution and maximum deformation. The corresponding correlations for the above characteristics are developed in this paper. Finally, the breakup regime map of CMC droplets is produced by the Weber number and the effective Ohnesorge number.